2014
DOI: 10.1159/000358436
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Ameliorates High-Glucose Toxicity in Rat Peritoneal Mesothelial Cells by Attenuating Oxidative Stress

Abstract: Background/Aims: Continuous exposure of the peritoneal membrane to high-glucose (HG) peritoneal dialysis fluids (PDFs) can produce peritoneal mesothelial cells (PMCs) injury. It has been demonstrated that hydrogen sulfide (H2S), the third endogenous gaseous mediator identified after nitric oxide and carbon monoxide, exhibits a potent protective effect on cell activity. We studied the toxic effects of HG PDFs and their reversal by H2S on cultures of rat PMCs. Methods: Synchronized confluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…We suppose that high glucose may, at least partly, play a crucial role as an oxidant, as reported elsewhere [ 11 13 ], which indicates room for improvement in the biocompatibility of the present standard solutions. Studies on clinical approaches to peritoneal protection have been limited so far [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that high glucose may, at least partly, play a crucial role as an oxidant, as reported elsewhere [ 11 13 ], which indicates room for improvement in the biocompatibility of the present standard solutions. Studies on clinical approaches to peritoneal protection have been limited so far [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of PD are short lived due to the gradual loss of peritoneal function caused by high-glucose PDFs and frequent peritonitis [14,15]. In the present study, the rat model of peritoneal fibrosis was established by intraperitoneal injection of 4.25%-glucose PDFs and LPS.…”
Section: Discussionmentioning
confidence: 99%
“…26 A previous study confirmed that EMT of PMCs is generally regarded to be the result of oxidative stress; while, antioxidants effectively reverse the EMT in PMCs. 27 In fact, oxidative stress has also been proposed to play a major role in the development of peritoneal deterioration 28 and apoptosis. 29 Among Figure 2.…”
Section: Discussionmentioning
confidence: 99%